Pengemmbangan Media Pembelajaran Interaktif Berbasis Website Google Sites Pada Mata Pelajaran Perawatan Tangan dan Mewarnai Kuku (Manicure) di SMK Negeri 1 Lamongan - Sherlita Restu Khairina; Biyan Yesi Wilujeng; Fernanda, M.A. Hanny Ferry; Maspiyah (Program Studi Pendidikan Tata Rias, 2025)
This research is motivated by the need for innovation in learning media that is in line with technological advancements to improve the quality of learning in vocational schools. The purpose of this study is to develop and design interactive learning media based on websites with the Google Sites platform, specifically for the subject of hand care and nail coloring (manicure). Field observations found at SMKN 1 Lamongan, the use of technology in the learning process, especially in learning media, is still very suboptimal, and there is no learning media that supports students' learning styles. Specifically, the main purpose of this study is as follows: 1) to review the feasibility of Google Sites website-based learning media, 2) to measure student learning outcomes, and 3) to determine students' responses to the learning media. The research method used is R&D with the ASSURE development model. The research subjects consisted of 26 students from the XII TKKR class. Data were collected through expert validation, cognitive tests (pre-test and post-test), psychomotor tests, and student response questionnaires. The validation results of the media feasibility showed an average score of 4.41 (88%) with the category